Wireless Application for Ordering Management System in A Restaurant - James Purnama; Andrea Yunita Wibowo (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2007)
The primary purpose of this application is to build a PDA (Personal Data Assistance) utility forordering in a restaurant. The benefits of implementing PDA on ordering management system in a restaurantare to make the waiters or waitresses’ works more efficient and also to make the orders more organized. Thefinding from this project is that PDA as a smart client has several benefits compare to other ordering systemin a restaurant. The conclusion of this project is that implementing PDA with its wireless technology onordering management system in a restaurant will improve the restaurant service.Keywords: Wireless Application, Personal Data Assistance, Ordering System.